Antibacterial Activity of Ethanol Extract of Purple Kencana Leaves (Ruellia tuberosa L.) Using TLC-Bioautography and Agar Diffusion Methods - Sari, Felisa Ananda; Herwin, Herwin; Handayani, Selpida (Fakultas Farmasi, Universitas Muslim Indonesia, 2023)
Kencana Ungu Leaf (Ruellia tuberosa L.) is a traditional plant that has antibacterial activity. The purpose of this study was to determine the antibacterial activity of the ethanol extract of Kencana Ungu leaves (Ruellia tuberosa L.) using TLC-Bioautography and Agar Diffusion methods. Simplisia from Kencana Ungu leaves (Ruellia tuberosa L.) was extracted by maceration method and then evaporated to obtain a thick extract. Preliminary testing, namely the antibacterial screening test, active extract at a concentration of 0.5% against Escherichia coli, Shigella dysenteriae, and Salmonella thypi. The results of the antibacterial activity test using the TLC-Bioautography method using chloroform: methanol (7:1) as an eluent showed results with an Rf value of 0.89 which inhibited the growth of Escherichia coli, Shigella dysenteriae, and Salmonella thypi bacteria. While the results of testing the antibacterial activity using the Agar Diffusion method obtained the largest diameter of the inhibition zone at a concentration of 20% for Escherichia coli bacteria with an inhibition zone diameter of 12.15 mm, Shigella dysenteriae with an inhibition zone diameter of 11.72 mm, and Salmonella thypi with an inhibition zone diameter of 12.67 mm